CULTURAL COMPETENCE IN ENGINEERING ENGLISH EDUCATION - Tegamuni, Suhaimi; Arif, Nutfah A.M (Humano: Jurnal Penelitian, 2024)
Cultural understanding in English language education for engineering is crucial in today's globalized world. Engineers need to not only be knowledgeable in their field but also understand different cultures to communicate and work effectively. Proficiency in English is essential for engineers as it is a common language in the industry. Cultural competence involves being able to interact well with people from diverse backgrounds. Research shows that those with high cultural competence can manage conflicts and collaborate better. The aim of this study is to explore how cultural understanding impacts English language learning in engineering and how it can be improved in the curriculum. Teaching strategies that promote cultural competence are important for students to succeed in multicultural work environments. Incorporating cultural elements into the curriculum can help students understand how culture influences communication and collaboration. Social learning and constructivist theories can aid in teaching cultural competence in English education for engineering. A descriptive qualitative approach is used to study cultural competence in English education for engineering, with participants from engineering student of Sekolah Tinggi Teknik Atlas Nusantara. The research involves analyzing qualitative data to gain a comprehensive understanding of cultural competence in education. Findings suggest that cultural competence positively influences English language proficiency in engineering students. Recommendations include integrating cultural competence into the curriculum and adopting interactive teaching methods to enhance cross-cultural understanding for students in the engineering field.